ジュウリョク カラ ミタ ショウワ キチ シュウヘン ノ チケイ ノ トクチョウ トク ニ タイリク ノ キバン チケイ ニ ツイテ - 長尾, 年恭; ナガオ, トシヤス; Nagao, Toshiyasu (1984)
P(論文) 第22次観測隊で行われた昭和基地周辺の重力測定結果からreduced gravity anomalyを求め, 基盤岩地形との相関係数を計算して, 重力から見た基盤岩地形および上部地殻構造の特徴の比較を試みた。比較した地域は, リュツォ・ホルム湾内の露岩地域, 海氷上, やまと山脈地域内の露岩地域, そしてアイスレーダーで氷厚の示されている昭和基地-みずほ基地ルートの一部地域である。結果は露岩地域, 海氷上では, いずれも予想されるとおり, 地形との正の相関が示された。しかし, 昭和基地-みずほ基地ルートでは, データのばらつきが大きく, しかも負の相関を示した。このことは, アイスレーダーで示された基盤岩地形を重力測定結果から解釈すると, モホ面が水平でなく, かつ凹凸していることに相当する。しかし, 他の地域ではそのようなことはなく, これはアイスレーダーの反射記録の解釈に原因があるのかもしれない。 The coefficients of the correlation between the reduced gravity anomaly and the bedrock height were calculated using gravity data in the Lutzow-Holm Bay region and the Mizuho Plateau, East Antarctica. A good positive relationship between the bedrock height and the reduced gravity anomaly was found on the sea ice and in the ice-free area of Lutzow-Holm Bay and in the ice-free area of the Yamato Mountains. On the contrary, the correlation between the reduced gravity anomaly and the bedrock height at gravity stations on the ice sheet whose ice thickness was measured by an ice radar survey showed a weak negative relationship. This fact may suggest that the determination of ice thickness by an ice radar on the ice sheet was inaccurate. The negative relationship between the reduced gravity anomaly and the bedrock height in the Mizuho Plateau means that the isostasy of this area is incomplete. departmental bulletin paper